Informatics in Control, Automation and Robotics - Filipe, Joaquim (Springer, 2012)
The present book includes a set of selected papers from the fourth "International Conference on Informatics in Control Automation and Robotics" (ICINCO 2007), held at the University of Angers, France, from 9 to 12 May 2007.